P5.033 Bringing HIV Testing to the People- Benefits of Mobile Unit Testing in Lima, Peru, 2007–2009. (13th July 2013) - Lipsitz, M C; Segura, E R; Anton, C; Castro, J; Clark, J L; Lake, J E; Cabello, R
Abstract : Background: Mobile unit (MU) HIV testing is an alternative method of providing healthcare access. We compared demographic and behavioural characteristics, HIV testing history, and HIV prevalence between people seeking testing at a MU vs. fixed community clinic (FC) in Lima, Peru. Methods: Our analysis included men and transwomen (TW) in Lima ≥ 18 years old seeking HIV testing at their first visit to a community-based clinic's MU or FC from Oct. 2007-Nov. 2009. Behavioral characteristics, including HIV testing history, and HIV serostatus of the following populations were compared in MU vs. FC attendees: TW, men who have sex with men (MSM), and heterosexually self-identified men who have sex with men and women (MSMW). Results: A greater percentage of MU attendees self-identified as transgender (8% vs. 3% FC, p < 0.05) or heterosexual (52% vs. 15% FC, p < 0.05). MU and FC sites attracted similar proportions of MSMW (52% MU vs. 57% FC). MU attendees were more likely to engage in compensated sex (10% MU vs. 4% FC, p < 0.05), not use condoms during their last sexual encounter (64% MU vs. 45% FC, p < 0.05), and be a first-time HIV tester (50% MU vs. 41% FC, p < 0.05; see Table 1). MU HIV prevalence was 5% (vs. 17% FC, p < 0.05). Among first-time testers, HIV prevalence in both MSM and TW was not significantly different between MU and FC attendees (MSM: 13% MU vs. 19% FC p = 0.14; TW: 41% MU vs. 50% FC p = 0.71). Conclusion: MU testing reached large numbers of high-risk (TW/MSM) and potentially bridging (MSMW) populations engaged in unsafe sexual behaviours. MU HIV prevalence for MSM/TW first-time testers was similar to that of the FC, making MU outreach a worthy complement to FC testing. Further investigation into whether MU attendees would not otherwise access HIV testing is warranted to determine the impact of MU testing.